2019
DOI: 10.2147/ott.s193097
|View full text |Cite
|
Sign up to set email alerts
|

<p>MiR-155-5p accelerates the metastasis of cervical cancer cell via targeting TP53INP1</p>

Abstract: Background: The dysregulation of microRNAs has been implicated in the progression of different malignancies. Herein, we sought to identify the precise roles of miR-155-5p in the progression of cervical cancer. Materials and methods: The expressions of miR-155-5p in cervical carcinoma cells and clinical tissues were assessed using qRT-PCR analysis. The functions of miR-155-5p on the growth of cervical cancer cell were investigated using MTT and colony formation. The Transwell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 34 publications
8
46
0
Order By: Relevance
“…miR-155 is previously identified as an oncogenic miRNA in various cancers, such as breast cancer, ovarian cancer and lung cancer. [32][33][34] In our work, we observed that miR-155 was upregulated in both M2 TAMs and exosomes secreted by M2 TAMs. Moreover, the function of exosomes secreted by M2 TAMs in NSCLC metastasis was mediated by miR-155, which modulated RASSF4 in NSCLC cells.…”
Section: Discussionsupporting
confidence: 53%
“…miR-155 is previously identified as an oncogenic miRNA in various cancers, such as breast cancer, ovarian cancer and lung cancer. [32][33][34] In our work, we observed that miR-155 was upregulated in both M2 TAMs and exosomes secreted by M2 TAMs. Moreover, the function of exosomes secreted by M2 TAMs in NSCLC metastasis was mediated by miR-155, which modulated RASSF4 in NSCLC cells.…”
Section: Discussionsupporting
confidence: 53%
“…Recently, the involvement of miRNAs in tumorigenesis and their signi cance as effective biomarkers are also becoming increasingly appreciated [14]. miR-155-5p has been found to regulate the development of various cancer types, including human epithelial ovarian cancer [16], cervical cancer [17,18], and colon cancer [19]. It has been reported that some certain long non-coding RNAs (lncRNAs) suppress HCC development by sponging miR-155-5p [20]; miR-155-5p modulated the malignancy of HCC by regulating Wnt/β-catenin signaling or suppressing PTEN through the PI3K/Akt pathway [21,22]; therefore, miR-155-5p can be a promising therapeutic target for HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 ] In cervical cancer, miR-155 promotes malignant tumor cell phenotypes through direct targeting of TP53INP1. [ 21 ] Additionally, miR-155 is overexpressed in AML and was identified as a potential biomarker for detecting AML. [ 22 ] Wang [ 23 ] et al demonstrated that miR-146a can promote cell proliferation and suppresses cell apoptosis via the downregulation of CNTFR in AML and ALL.…”
Section: Discussionmentioning
confidence: 99%